Kinetic studies and predictions on the hydrolysis and aminolysis of esters of 2-S-phosphorylacetates - Trmčić, Milena; Hodgson, David R. W. (Beilstein Journal of Organic Chemistry, 2010)
Background: Heterobifunctional cross-linking agents are useful in both protein science and organic synthesis. Aminolysis of reactive esters in aqueous systems is often used in bioconjugation chemistry, but it must compete against hydrolysis processes. Here we study the kinetics of aminolysis and hydrolysis of 2-S-phosphorylacetate ester intermediates that result from displacement of bromide by a thiophosphate nucleophile from commonly used bromoacetate ester cross-linking agents.Results: We found cross-linking between uridine-5′-monophosphorothioate and D-glucosamine using N-hydroxybenzotriazole and N-hydroxysuccinimde bromoacetates to be ineffective. In order to gain insight into these shortfalls, 2-S-(5′-thiophosphoryluridine)acetic acid esters were prepared using p-nitrophenyl bromoacetate or m-nitrophenyl bromoacetate in combination with uridine-5′-monophosphorothioate. Kinetics of hydrolysis and aminolysis of the resulting p- and m-nitrophenyl 2-S-(5′-thiophosphoryluridine)acetates were determined by monitoring the formation of phenolate ions spectrophotometrically as a function of pH. The p- and m-nitrophenyl 2-S-(5′-thiophosphoryluridine)acetates showed similar reactivity profiles despite the significant difference in the pKaH values of their nitrophenolate leaving groups. Both were more reactive with respect to hydrolysis and aminolysis in comparison to their simple acetate progenitors, but their calculated selectivity towards aminolysis vs hydrolysis, while reasonable, would not lead to clean reactions that do not require purification. Extrapolations of the kinetic data were used to predict leaving group pKa values that could lead to improved selectivity towards aminolysis while retaining reasonable reaction times.Conclusions: Both p- and m-nitrophenyl 2-S-(5′-thiophosphoryluridine)acetates show some selectivity towards aminolysis over hydrolysis, with the m-nitrophenolate system displaying slightly better selectivity. Extrapolation of the data for hydrolysis and aminolysis of these esters suggests that the use of readily accessible trifluoroethyl 2-S-(5′-thiophosphoryluridine)acetate with a leaving group pKaH of 12.4 should afford better selectivity while maintaining reasonable reaction times. Kinetically, p- and m-nitrophenyl 2-S-(5′-thiophosphoryluridine)acetates show similar properties to o-nitrophenyl 2-S-ethylacetate, and show no evidence for intramolecular catalysis of hydrolysis or aminolysis by the phosphoryl groups.
Keywords: aminolysis; heterobifunctional cross-linker; hydrolysis; kinetics; thiophosphate